2023
DOI: 10.1186/s13578-023-01150-z
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and stable spontaneous reprogramming system of Spermatogonial stem cells to Pluripotent State

Rui Wei,
Xiaoyu Zhang,
Xiaoxiao Li
et al.

Abstract: Background The scarcity of pluripotent stem cells poses a major challenge to the clinical application, given ethical and biosafety considerations. While germline stem cells commit to gamete differentiation throughout life, studies demonstrated the spontaneous acquisition of pluripotency by spermatogonial stem cells (SSCs) from neonatal testes at a low frequency (1 in 1.5 × 107). Notably, this process occurs without exogenous oncogenes or chemical supplementation. However, while knockout of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…These findings not only provide valuable insights into the nuanced protein expression profiles but also serve as supportive evidence for our in silico analysis, wherein Nanog emerged as a pivotal and differentially expressed gene during the transformation of SSCs into ES-like cells. Previous studies reported that there is a higher concentration of Nanog and other pluripotent factors in ES-like cells than SSCs [29][30][31] The expression status of the Nanog gene among ES-like cells derived from SSCs has been assessed in previous studies with a comparative perspective. As far as we know, most but not all of these studies have reported a higher Nanog gene expression or protein concentration by in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…These findings not only provide valuable insights into the nuanced protein expression profiles but also serve as supportive evidence for our in silico analysis, wherein Nanog emerged as a pivotal and differentially expressed gene during the transformation of SSCs into ES-like cells. Previous studies reported that there is a higher concentration of Nanog and other pluripotent factors in ES-like cells than SSCs [29][30][31] The expression status of the Nanog gene among ES-like cells derived from SSCs has been assessed in previous studies with a comparative perspective. As far as we know, most but not all of these studies have reported a higher Nanog gene expression or protein concentration by in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%